Induction of antibody to asialo GM1 by spermatozoa and its occurrence in the sera of homosexual men with the acquired immune deficiency syndrome (AIDS). - Witkin, S S (1983)
Compared to healthy homosexual and heterosexual men, homosexual men with acquired immune deficiency syndrome (AIDS) possessed significantly higher levels of IgG antibody to the neutral glycolipid asialo GM1 (ganglio-N-tetraosylceramide) (P less than 0.01). Of 31 homosexuals with AIDS, 36% possessed levels of this antibody that were at least two standard deviations above the mean of the healthy men. Furthermore, asialo GM1 antibody could be removed from serum by adsorption with spermatozoa. Weekly rectal insemination of male rabbits with rabbit semen also led to the appearance of antibody to asialo GM1 by 15 weeks. These results suggest that asialo GM1 is a component of ejaculated spermatozoa and demonstrate that rectal insemination by itself can lead to the production of antibodies to this glycolipid in the rabbit. In addition, asialo GM1 antibodies may be of value as a serological marker for the early detection of individuals with AIDS.